Use of xenogeneic vaccine modified with embryonal nervous tissue antigens in the treatment of B16‑melanoma-bearing mice - Voeykova, І.М.; Fedosova, N.І.; Karaman, О.М.; Yudina, О.Y.; Didenko, G.V.; Lisovenko, G.S.; Evstratieva, L.М.; Potebnya, G.P. (Experimental Oncology, 2014)
The aim of the work was experimental study of anticancer efficacy of xenogeneic cancer vaccine (XCV) developed on the basis of rat embryonic nervous tissue and protein-containing metabolite of Bacillus subtilis В-7015 (70 kDa), in В-16 melanoma-bearing С57Bl/6 mice. Methods: Immunological methods and methods of experimental oncology were used. Effects of XCV on primary and secondary organs of immune system of experimental animals, its anticancer and antimetastatic efficacy were evaluated. Results: It has been shown that XCV did not induced toxic effects on organism, and did not caused inflammatory reactions. The relation between the degree of XCV anticancer efficacy with the regimen of its use and the presence of primary tumor has been analyzed. It has been demonstrated that the developed XCV possesses significant antimetastatic activity if it is used after surgical removal of the primary tumor: in this case lung metastasis inhibition index reached 97.4%. Conclusion: High immunogenecity of new XCV creates perspectives for detailed study of its mechanisms of action. Key Words: oncofetal antigens, xenogeneic cancer vaccine, В-16 melanoma, immunotoxicity, effectors of anticancer defence.